In conversation. Issue 1 (1st August 2020) - Vaidyanathan, Rama; Viswanath, Kaladharan
Rama Vaidyanathan is a leading exponent of Bharatanatyam, a popular classical dance form of South India. Trained under the renowned Guru Saroja Vaidyanathan and the legendary dancer Yamini Krishnamurthy, Rama Vaidyanathan is undoubtedly one of the most profound performers of her generation in the world of dance in India. Kaladharan Viswanath is a leading writer and dance critic and their conversation reveals some deeper insights into the philosophy and practice of Rama Vaidyanathan's dance and its intersection with music.